Pemetaan Pm10 Dan Aot Menggunakan Teknik Penderiaan Jauh Di Semenanjung Malaysia - San, Limhwee (2006)
This study is dealing with retrieving concentrations of particles with diameters less than 10 micrometer (PM10) in the atmosphere. The objective of this study is to develop an algorithm based on the aerosol optical thickness (AOT) for mapping PM1 0 using digital camera and satellite imageries. The developed algorithms are two-band algorithm, terma linear and modified algorithm from the combination of the visible and infrared thermal bands. In this study, satellite and airborne digital images were captured by a normal digital camera from a low-altitude flying aircraft to generate PM10 and AOT maps of Peninsular Malaysia. In-situ PM1 0 measurements were collected simultaneously with the digital image acquisition using a DustTrak Aerosol Monitor model 8520 and their locations were determined by a handheld global positioning system (GPS). The retrieval of surface reflectance is important to obtain the atmospheric reflectance in remotely sensed data and later used for algorithm calibration. In this study, two techniques were used to retrieve the surface reflectance, dark target technique and A TCOR2 technique. Dark target technique uses the relationship between two visible bands (blue and red) and the mid infrared data at 2.1 !Jm. The coefficient of the relationship between the mid infrar~d band and visible band (blue and red) was obtained using the plotted graph. A handheld spectroradiometer '.•tas used fer surface reflectance and transmittance measurements in the visible wavelength. AOT values were calculated based on the Beer-Lambert-Bouguer law. The digital numbers of the required bands corresponding to the in-situ locations were extracted and then converted into reflectance values for algoritma calibration. The atmospheric reflectance values was obtained by subtrating the amount given by the surface reflectance from the satellite observation reflectance values. Various algorithms were then examined by comparing the correlation coefficient (R) values and xxix the root-mean-square (RMS) error values. The two-band model, terma linear and modified algorithms were selected based on the highe.st correlation coefficient (R) value {> 80%) and the lowest root-mean-square (RMS) error value. The proposed algorithms were used to generate PM10 and AOT maps for the study areas. The maps were geometrically corrected and colour coded for visual interpretation to the PM10 and AOT distributions patterns. Average filtering was applied to the PM10 map to mininise the noise effect. The proposed algorithms were also validated using the multidate data. The validation analysis produced high correlation coefficient value(> 80%). Besides that, interpolate technique was also used in this study for AOT mapping using in situ data. Three techniques were performed in this study to retrieve the reflectance values from the horizontal digital camera imageries. They were reference technique, far-near distance technique and flat-field technique. The reference technique proposed in this study used a dark card as reference and this technique produced the high accuracy compared to other two techniques. The two techniques proposed to retrieve surface reflectance from the vertical digital camera imageries were (i) classification technique and (ii) by using a surface reflectance map derive from A TCOR2.